Description of Three Novel Members in the Family Geobacteraceae, Oryzomonas japonicum gen. nov., sp. nov., Oryzomonas sagensis sp. nov., and Oryzomonas ruber sp. nov. - Zhenxing Xu; Yoko Masuda; Chie Hayakawa; Natsumi Ushijima; Keisuke Kawano; Yutaka Shiratori; Keishi Senoo; Hideomi Itoh (Microorganisms, 2020)
Bacteria of the family Geobacteraceae are particularly common and deeply involved in many biogeochemical processes in terrestrial and freshwater environments. As part of a study to understand biogeochemical cycling in freshwater sediments, three iron-reducing isolates, designated as Red96T, Red100T, and Red88T, were isolated from the soils of two paddy fields and pond sediment located in Japan. The cells were Gram-negative, strictly anaerobic, rod-shaped, motile, and red-pigmented on agar plates. Growth of these three strains was coupled to the reduction of Fe(III)-NTA, Fe(III) citrate, and ferrihydrite with malate, methanol, pyruvate, and various organic acids and sugars serving as alternate electron donors. Phylogenetic analysis based on the housekeeping genes (16S rRNA gene, gyrB, rpoB, nifD, fusA, and recA) and 92 concatenated core genes indicated that all the isolates constituted a coherent cluster within the family Geobacteraceae. Genomic analyses, including average nucleotide identity and DNA–DNA hybridization, clearly differentiated the strains Red96T, Red100T, and Red88T from other species in the family Geobacteraceae, with values below the thresholds for species delineation. Along with the genomic comparison, the chemotaxonomic features further helped distinguish the three isolates from each other. In addition, the lower values of average amino acid identity and percentage of conserved protein, as well as biochemical differences with their relatives, indicated that the three strains represented a novel genus in the family Geobacteraceae. Hence, we concluded that strains Red96T, Red100T, and Red88T represented three novel species of a novel genus in the family Geobacteraceae, for which the names Oryzomonas japonicum gen. nov., sp. nov., Oryzomonas sagensis sp. nov., and Oryzomonas ruber sp. nov. are proposed, with type strains Red96T (= NBRC 114286T = MCCC 1K04376T), Red100T (= NBRC 114287T = MCCC 1K04377T), and Red88T (= MCCC 1K03694T = JCM 33033T), respectively.